INTERREGIONAL THE TRAVEL INDUSTRY CHAIN ENHANCEMENT DEPENDENT ON FRAMEWORK ELEMENTS - WANG Ling (International Scientific and Current Research Conferences, 2021)
The improvement of transportation industry, space distance in time was incredibly abbreviated, the gigantic ascent of territorial the travel industry action in various space of the connection between the travel industry ventures of the undeniably close; In this specific circumstance, the current the travel industry tie is hard to adjust to the requirements of new circumstance, should be upgraded and rebuilding. In light of the foundation of interregional the travel industry chain, based on the advancement objective, utilizing framework elements technique, developed the interregional the travel industry chain enhancement model, and the model was tried and assessed.